Kokkuvõte kliinilisest auditist „Depressiooni diagnostika ja ravi esmatasandil“ - Puis, Liis; Suija, Kadri; Ööpik, Pille; Lomp, Ülle; Meister, Tatjana; Kivisto, Katrin (Eesti Arst, 2017)
Eesti Arst 2017; 96(2):69–72